Zimbabwe Diagnostic Review of Consumer Protection and Financial Literacy : Volume 1. Key Findings and Recommendations - World Bank Group (World Bank, Washington, DC, 2017)
In the last decade, Zimbabwe’s financial sector survived the periods of hyperinflation and the collapse of the national currency that led to the adoption of a multi-currency system in early 2009. Consequently, financial sector activity in Zimbabwe has shrunk by more than 50 percent in many segments. In 2015, the financial sector is dominated by the banking segment that is generally stable but faces major systemic challenges: low liquidity, low capitalization, high cost of funds with low domestic savings and expensive external borrowing. High credit risks increase the reluctance to lend. At the same time, the technology-driven segments are growing rapidly but regulatory gaps pose significant systemic and entity-level risks. In such circumstances, the Zimbabwe authorities recognize the urgency of establishing a sound financial consumer protection regime and promoting financial literacy. This World Bank’s diagnostic review was requested by the Reserve Bank of Zimbabwe with support of the national government and regulatory bodies. It provides analysis of the legal and regulatory framework in the banking, digital financial services, non-bank credit institutions, insurance, securities, private pensions, and credit reporting segments. Four consumer focus groups were also conducted on financial capability issues. Volume I of the Review summarizes the key findings and recommendations, and Volume II provides comparison with the Good Practices for Financial Consumer Protection.